The crucial role the field epidemiology training program played in preparedness and response to the COVID-19 pandemic in Sierra Leone, January 2020 to August 2022 - Gebru, Gebrekrstos Negash; Henderson, Alden Keith; Elduma, Adel Hussein; Squire, James Sylvester; Vandi, Mohamed Alex; Moffett, Daphane; Foster, Monique (Frontiers in Public Health, 2025)
BackgroundOn January 30, 2020, the World Health Organization declared COVID-19 a Public Health Emergency of International Concern (PHIEC). On March 11, 2020, it was characterized as a pandemic, prompting the Government of Sierra Leone to implement response plans. The first case in the country was reported on March 31, 2020. To build resilient public health systems after the Ebola crisis, the Sierra Leone Field Epidemiology Training Program (SLFETP) was launched in 2016 with funding from the U.S. CDC in collaboration with the Ministry of Health and the African Field Epidemiology Network (AFENET). The program started at the FETP Frontline level, a 3-month in-service training program, followed by the FETP Intermediate, a 9-month in-service training program launched in 2017. Both levels adopted the CDC curriculum to the local context. The curriculum consists of classroom modules focusing on surveillance, outbreak investigation, and field projects. The SLFETP graduates and trainees were deployed to assist in COVID-19 response efforts. While reports indicate the SLFETP's contributions to COVID-19 preparedness and response, the specific roles of its graduates and trainees remain undocumented. This paper outlines their crucial involvement during the pandemic in Sierra Leone.MethodsWe reviewed 12 documents from the SLFETP, including work plans, outbreak investigation reports, and success stories, to assess the FETP's contributions during the COVID-19 pandemic. We interviewed graduates and trainees about their roles and conducted discussions with stakeholders and FETP staff to explore the FETP's role during the pandemic's preparedness and response phases. A thematic analysis was performed.ResultsThe SLFETP played a critical role during the preparedness and response phase of the COVID-19 pandemic. The trainees and graduates enhanced the surveillance system and led key response pillars, such as coordination, surveillance, and quarantine. SLFETP supported districts by building their capacity, especially in the district surveillance pillar, to conduct case investigations, contact tracing, quarantine monitoring, and data management.ConclusionsThe graduates and trainees reportedly played critical roles in key response pillars across the country in the preparedness and response phase of the COVID-19 pandemic. These gains should be maintained and scaled up to build a strong and resilient public health workforce in Sierra Leone, which is crucial for preparedness and response to future outbreaks.